2019
DOI: 10.1101/714451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term block of CRH receptor in adults mitigates age-related memory impairments provoked by early-life adversity

Abstract: In humans, early-life adversity (ELA) is associated with impairments in learning and memory that may emerge later in life. In rodent models, ELA directly impacts hippocampal neuron structure and connectivity with progressive deficits in long-term potentiation and spatial memory function. Previous work has demonstrated that augmented release and actions of the stressactivated neuropeptide, CRH, contribute to the deleterious effects of ELA on hippocampal structure and memory-function. Early-life adversity increa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Also, high levels of glucocorticoids may accelerate the aging process, by causing further damage to the hippocampus and increasing the exposure to exaggerated inflammatory responses such as priming of microglia (Landfield et al, 2007;Barrientos et al, 2015a,b). Moreover, stressful experiences in early life also enhance and accelerate the aging process in the hippocampus and the cognitive functions it supports (Lupien et al, 1999;Kumar, 2011;Sousa et al, 2014;Short et al, 2020), while manipulations early in life that reduce corticosterone levels in rodents reduce memory impairments later in life (Meaney et al, 1988; for review see Lesuis et al, 2018). Together, these studies suggest that adverse (stressful) environmental experiences can accelerate age-related decline in hippocampal cognitive function.…”
Section: Larger-scale Neural Systems: the Hippocampal Systemmentioning
confidence: 84%
“…Also, high levels of glucocorticoids may accelerate the aging process, by causing further damage to the hippocampus and increasing the exposure to exaggerated inflammatory responses such as priming of microglia (Landfield et al, 2007;Barrientos et al, 2015a,b). Moreover, stressful experiences in early life also enhance and accelerate the aging process in the hippocampus and the cognitive functions it supports (Lupien et al, 1999;Kumar, 2011;Sousa et al, 2014;Short et al, 2020), while manipulations early in life that reduce corticosterone levels in rodents reduce memory impairments later in life (Meaney et al, 1988; for review see Lesuis et al, 2018). Together, these studies suggest that adverse (stressful) environmental experiences can accelerate age-related decline in hippocampal cognitive function.…”
Section: Larger-scale Neural Systems: the Hippocampal Systemmentioning
confidence: 84%
“…As regards the time frame during which interventions might be effective, studies in orphans suggested that cognitive recovery is lower in individuals who were provided with adoptive families later than 24 months of age than in infants who were adopted earlier 25,29 . Similarly, in experimental models, early interventions using pharmacological and epigenetic approaches enabled restoration of memory in adversity-experiencing rats 91,122 , whereas later interventions were less effective 243 . Together, these findings suggest that lengthening the sensitive period when neuronal and circuit plasticity enables intervention would be a major advance in post hoc interventions after early-life adversity.…”
Section: Potential Interventionsmentioning
confidence: 99%